Determination of method-invariant activation energies of long-chain branched low-density polyethylenes - Keßner, Ute; Kaschta, Joachim; Münstedt, Helmut (Journal of Rheology, 2009)
The idea to use the temperature dependence of rheological properties, especially the flow activation energy, as a tool to investigate branching structures is well-known from literature. However, there is no common method to obtain activation energies, which are independent of the measuring quantity chosen, particularly, in the case of slightly thermorheologically complex polymers like low-density polyethylene (LDPE). Hence, differing activation energies result, which cannot unequivocally be correlated with the branching structure. This paper describes a method for the determination of method-independent activation energies for thermorheologically complex polymers like LDPE. From a generalized approach to the time-temperature superposition principle, a vertical shift factor is introduced, which is related to the temperature dependence of the linear steady-state compliance. In the case of the complex LDPE, a decrease in the linear steady-state compliance with temperature is found. Taking this experimentally determined shift factor into account leads to activation energies independent of the rheological quantity chosen. These values can be taken to analyze differences of the branching architecture.
Keywords: polymer melts; rheology; viscoelasticity